THE CONCEPT OF RISK MANAGEMENT IN MICRO FINANCING FOR ASNĀF ENTREPRENEURS FROM AN ISLAMIC PERSPECTIVE - Zainal, Nurul Najibah; Ghazali, Nooramira; Khairuldin, Wan Mohd Khairul Firdaus Wan; Sabri, Siti Aisyah; Aziz, Ahmad Azizi (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
The distribution of zakat funds through microcredit financing has emerged as an innovative strategy implemented by zakat institutions to empower the asnāf community. However, there are issues among scholars regarding tamlīk (ownership) and zakat in such arrangements. There is an opinion that zakat distribution should not require repayment due to concerns about the potential failure of the asnāf entrepreneur to repay the loan within the stipulated time period. This study aims to explore the risk management strategies for asnāf entrepreneur microfinancing from an Islamic perspective and analyze the application of Sharia compliant approaches to modern risk management practices. The research utilizes document analysis and content analysis to gather and interpret data. These findings contributes treasured insights into the improvement of more effective and equitable microcredit applications for the asnāf network, helping to empower asnāf entrepreneurs and alleviate poverty in a way consistent with Islamic values. This research hopes to strengthen the management and implementation of microcredit programs for asnāf entrepreneurs.